2019
DOI: 10.1016/j.powtec.2019.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Modeling granular material segregation using a combined finite element method and advection–diffusion–segregation equation model

Abstract: A two-dimensional, transient, multi-scale modeling approach is presented for predicting the magnitude and rate of percolation segregation for binary mixtures of granular material in a rotating drum and conical hopper. The model utilizes finite element method simulations to determine the bulk-level granular velocity field, which is then combined with particle-level diffusion and segregation correlations using the advection-diffusion-segregation equation. The utility of this modelling approach is demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…More complex models that do use a continuum approach to calculate the bulk flow in a circular drum (e.g. Liu, Gonzalez & Wassgren 2018, 2019), do so with rate-independent elasto-plastic constitutive laws which are prone to ill posedness (Schaeffer 1987). This paper goes considerably further, by using the partially regularized -rheology and the recent segregation model of Trewhela et al.…”
Section: Fully Coupled Rotating Drum Simulationsmentioning
confidence: 99%
“…More complex models that do use a continuum approach to calculate the bulk flow in a circular drum (e.g. Liu, Gonzalez & Wassgren 2018, 2019), do so with rate-independent elasto-plastic constitutive laws which are prone to ill posedness (Schaeffer 1987). This paper goes considerably further, by using the partially regularized -rheology and the recent segregation model of Trewhela et al.…”
Section: Fully Coupled Rotating Drum Simulationsmentioning
confidence: 99%
“…1998; Fan et al. 2012), silos (Bates 1997; Schulze 2008; Liu, Gonzalez & Wassgren 2019; Isner et al. 2020) and rotating tumblers (Gray & Hutter 1997; Hill et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods have not become widely used since the accuracy of numerical calculations is significantly limited due to the pre-uncertain initial conditions and the non-physical nature of boundary conditions [25]. The results reported in works [22][23][24][25] are typical of the operation of drum mixers without blades and when mixing materials that have a defined granulometric composition of the mixture components. The use of the reported models to describe the process of agitating organic compost would lead to significant deviations from the given results.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Both the low reliability of control devices and the complexities of mathematical calculations reduce the effectiveness of known techniques to determine the kinematic parameters of the movement of the particle of the material in a rotating drum. Therefore, the analytical and experimental studies' results, reported in works [15][16][17][18][19][20][21][22][23][24][25][26][27], are approaching the actual modes of movement of the studied environment only in terms of external features and qualitative characteristics. In addition, they mainly relate to dry loose materials.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation